Retrospective review of wild waterfowl diseases in Kansas - Becker, Thomas Allen (Kansas State University, 2016)
There is a wide variety of diseases that affect wild migratory birds. Occurrence, causes, and impacts of disease outbreaks in wild bird populations are rarely studied beyond documentation of large epizootic events. The relationships between the wildlife-livestock-human interface is rapidly blurring together. Global interests in avian diseases increased around 1990 as a result of the prevalence of zoonosis and potential threat to domestic livestock. A central disease reporting protocol does not exist in many states, which has led to a lack of available historical knowledge of disease occurrence that could be used to predict and manage future outbreaks. Due to changes of abundance and distribution of the migrant populations of Ross’s goose (Chen rossii) and Snow goose (C. caerulescens), geese are increasing their stopover duration in Kansas potentially increasing risk of disease outbreaks. We compiled historic records of wild waterfowl disease events in Kansas from 1967-2014 and related the frequency of events with indices of light geese abundance from 1970-2014. We found 32 reports spanning 16 counties consisting of the diseases avian cholera, avian botulism, aspergillosis, renal coccidiosis, west Nile, aflatoxicosis, and mycotoxicosis. Using a retrospective survey, we found there was a significant relationship between population densities of light geese in Kansas during the Mid-Winter Waterfowl Inventory and occurrence of avian cholera. Efforts to increase the understanding of relationships between disease outbreaks and host species will improve management of future disease outbreaks. Understanding factors known to facilitate wild waterfowl disease events (e.g., environmental, species, and individual), may assist in disease identification and determine a disease management course of action. This course of action is predetermined in a disease management plan. Disease management plans should be developed at the state and station level; incorporating planning, response, disease control, and surveillance and monitoring schemes to build upon the centralized disease database and to promote future disease understanding.
Keywords: Avian CholeraWaterfowl disease; Avian Botulism; Kansas; Disease management plan